Pengaruh Manajemen Kelas dan Motivasi Belajar Terhadap Hasil Belajar Matematika - Misyanto Misyanto (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This study aims to determine the effect of classroom management and motivation of learners towards mathematics learning outcomes of students in class V SD Se-Gugus VIII Palangka Raya.The research was done in Primary Schools Se-Gugus VIII Palangka Raya, Central Kalimantan in October in the school year 2014/2015 Semester I. This research sample class V SDN 6 Pahandut and SDS Muhammadiyah Pahandut by 45 respondents drawn by technique Cluster Sampling Area.This research method with survey method by using path analysis, which aims to examine: 1) the direct influence of the management class to the learning outcomes of students math class V SD Se-Gugus VIII Palangka Raya, 2) direct influence between motivation of learners to results students learn math class V SD Se-Gugus VIII Palangka Raya, and 3) direct influence of the management class to the motivation of learners. In this study, we can conclude that there is a direct influence of the management class for math learning outcomes of 0.324, there is a direct influence of motivation toward mathematics learning outcomes of 0.350, and there is a direct influence of the management class on motivation to learn at 0.496.